Assessment of potential toxicity of a smokeless tobacco product (naswar) available on the Pakistani market. Issue 4 (3rd June 2011) - Zakiullah; Saeed, Muhammad; Muhammad, Naveed; Khan, Saeed Ahmad; Gul, Farah; Khuda, Fazli; Humayun, Muhammad; Khan, Hamayun
Abstract : Background: 'Naswar' is a smokeless tobacco product (STP) widely used in Pakistan. It has been correlated with oral and oesophageal cancer in recent clinical studies. The toxic effects associated with STPs have been associated with trace level contaminants present in these products. The toxin levels of Pakistani naswar are reported for the first time in this study. Methods: A total of 30 Pakistani brands of naswar were tested for a variety of toxic constituents and carcinogens such as cadmium, arsenic, lead and other carcinogenic metals, nitrite and nitrate, and nicotine and pH. Results: The average values of all the toxins studied were well above their allowable limits, making the product a health risk for consumers. Calculated lifetime cancer risk from cadmium and lead was 1 lac (100000) to 10 lac (1000000) times higher than the minimum 10E _ 4 (0.00001) to 10E _ 6 (0.000001), which is the 'target range' for potentially hazardous substances, according to the US Environmental Protection Agency. Similarly, the level of arsenic was in the range of 0.15 to 14.04 μg/g, the average being 1.25 μg/g. The estimated average bioavailable concentration of arsenic is 0.125–0.25 μg/g, which is higher than the allowable standard of 0.01 μg/g. Similarly, the average minimum daily intake of chromium and nickel was 126.97 μg and 122.01 μg, as compared to allowable 30–35 μg and 35 μg, respectively; a 4–5 times higher exposure. However, beryllium was not detected in any of the brands studied. The pH was highly basic, averaging 8.56, which favours the formation of tobacco specific amines thus making the product potentially toxic. This study validates clinical studies correlating incidence of cancer with naswar use in Pakistan. Conclusions: This study shows that the production, packaging, sale and consumption of naswar should be regulated so as to protect the public from the health hazards associated with its consumption.